Prediction of Epitopes in the Proteome of Helicobacter pylori (2018)
Helicobacter pylori (H. pylori) is classified by the World Health Organization (WHO) as a group I carcinogen and is one of the most efficient human pathogens with over half of the world's population colonized by this gram-negative spiral bacterium. H. pylori can cause a chronic infection in the stomach during early childhood that persists throughout life due to diverse mechanisms of immune response evasion. H. pylori has several factors strongly associated with increased risk of disease such as toxins, adhesins, and chemoattractants, some of which are highly polymorphic, phase variable, and have different functions. Conventional treatments involve the use of antibiotics. However, treatment frequently fails due to the resistance H. pylori has progressively developed to antibiotics. This creates the need for different treatments made possible by identifying new therapeutic targets in the pathogen’s genome. The purpose of this study was an in silico prediction of T- and B- epitopes in H. pylori proteins. Twenty-two external membrane proteins from H. pylori Strain 26695 (accession number NC_000915) were identified using the web tool Vaxign (http://www.violinet.org/vaxign/). A total of one-hundred epitopes (60 class I epitopes and 40 class II epitopes) that could be used to develop novel non-antibiotics drugs for an H. pylori infection were predicted.